PROFIL SOSIAL KIAI KAMPUNG; DARI GURU NGAJI HINGGA PENJAGA TRADISI - Totok Agus Suryanto; Ruslan Ruslan; Abd. Muiz (Al-Amien Prenduan University, Sumenep, 2023)
Kiai is a central figure in the social life of Madurese society. Because, he represents a social profile that is irreplaceable as a significant other in the social environment of the community. Therefore, this study seeks to comprehensively discuss the profile of village kiai on the island of Madura, which has a very urgent role in the social process of the community where kiai live in it. Starting as a Quranic teacher to the guardian of tradition and agent of change. In the social process of living together in the community, kiai are in many ways the guardians of tradition and agents of change. As guardians of tradition, kiai become leaders of every social and religious event that has been deeply rooted in the traditions of the community. Rather than that, on the other hand, kiai also act as agents of change with the surrounding community in an effort to maintain and bring the community to the usual path based on the objectivation of values in society. In terms of methods, this research uses a descriptive type qualitative approach by means of observation, interviews and documentation.